1998
DOI: 10.1007/s005340050049
|View full text |Cite
|
Sign up to set email alerts
|

Modified hepatoduodenal ligamentectomy for advanced carcinoma of the biliary tract: The importance of preservation of the replaced left hepatic artery

Abstract: Hepatoduodenal ligamentectomy (ligamentectomy) is the ultimate surgery for biliary tract carcinoma involving perioperative difficulties such as total hepatic ischemia during revascularization of the hepatic artery and the portal vein, patency of the reconstructed hepatic artery, and high incidence of related operative mortality. In the present study, modified ligamentectomies with extended right hepatic lobectomy, including resection of the caudate lobe, were performed on three patients with advanced biliary t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 4 publications
(10 reference statements)
0
5
0
Order By: Relevance
“…Only a limited number of 5‐year survivors with LN metastasis have been reported to date, and Table 10 shows our 6 long‐term survivors with LN metastasis after resection. Of note, one patients whose 3 of 8 paraaortic LNs showed metastasis (8 of a total of 24 excised LNs revealed metastasis) is alive more than 14 years with no sign of recurrence after modified hepato‐ligamento‐pancreatoduodenectomy (Table 10) [26]. The fact that long‐term survival is possible even in pN 1 or pM 1 disease encourages surgeons to perform an aggressive surgical resection with extended LN dissection in selected patients with hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Only a limited number of 5‐year survivors with LN metastasis have been reported to date, and Table 10 shows our 6 long‐term survivors with LN metastasis after resection. Of note, one patients whose 3 of 8 paraaortic LNs showed metastasis (8 of a total of 24 excised LNs revealed metastasis) is alive more than 14 years with no sign of recurrence after modified hepato‐ligamento‐pancreatoduodenectomy (Table 10) [26]. The fact that long‐term survival is possible even in pN 1 or pM 1 disease encourages surgeons to perform an aggressive surgical resection with extended LN dissection in selected patients with hilar cholangiocarcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the width of the ligament, we found that there were two periods of accelerated development (4-5 months and 9 monthsnewborns) and a period of slow development (5-8 months). It is worth noting that at some stage of development (6 months), the length of the hepatic-duodenal ligament is even slightly reduced, which can probably be associated with an increase in the adjacent organs -the liver and the duodenum in this period [13][14][15][16][17][18][19][20].…”
Section: Discussionmentioning
confidence: 99%
“…In this event, it is virtually impossible to obtain tumor-free resection margins even after hepatoduodenal ligamentectomy, major hepatectomy with en bloc resection of the hepatic artery, portal vein and pancreas head, especially in terms of dissecting margins. In patients with replaced left hepatic artery arising from the left gastric artery, hepatic arterial reconstruction is unnecessary for hepatoduodenal ligamentectomy, and the success of R0 resection may be further assured by preserving the replaced arterial blood supply [71].…”
Section: Hepatic Arterymentioning
confidence: 99%